Cyto-Histo-Biochemical And Ultrasonographic Correlation of Thyroid Lesions –A Multidisciplinary Approach: An Experience at Rural Tertiary Care Hospital in Southern coast of India - Kotasthane, Vaishali Dhananjay; Kotasthane, Dhananjay Shrikant; Vaithy, Anandraj (Annals of Pathology and Laboratory Medicine, 2018)
Introduction: Thyroid lesions are one of the most common palpable lesions subjected for FNAC.Fine Needle Aspiration Cytology (FNAC) of the thyroid gland is now a well-established first-line diagnostic test for the evaluation of diffuses thyroid lesions as well as of thyroid nodules with the main purpose of confirming benign lesions and thereby, reducing unnecessary surgery.Apart from cytology, other investigations like ultrasonography (USG),thyroid function tests(TFTs) play a supportive for better understanding of thyroid nodules under evaluation.Also, there is some "gray zone" of thyroid cytology where the diagnostic efficacy of FNA declines sharply.Radioimaging (ultrasonography) can be helpful in grey areas of indeterminate lesions and non-diagnostic aspirates. Though USG features alone cannot predict malignancy or benignity, but techniques that combine USG features and FNA cytology are most effective and most accurate for predicting malignancy. Aims and Objectives:We aimed to evaluate cytological features of palpable thyroid lesions and to correlate with histopathological , radiological and thyroid function tests wherever available, at a rural tertiary health care institute in southern coastal region of India. Materials /methods:This study was analysis of 156 cases of palpable diffuse and nodular thyroid lesions subjected to FNAC over a period of one and half year at a rural tertiary health care Institute. Results:Thyroid lesions constituted 19.3% of total lesions subjected to FNAC in study period.Age group ranged from 13 - 77 years, maximum cases belonged to 5th decade with female preponderance . Clinically, nodular swelling accounted for 86% cases.Benign lesions detected were 75.6%. Malignant lesion accounted for 7.7% cases.Cyto-histo correlation overall was noted in 72.2% cases with benign lesions showed 76.92% were as malignant lesion showed 100% correlation. Sensitivity, specificity , positive predictive value, negative predictive value and diagnostic accuracy was 40%, 100%,100%, 78.6% and 81.3% respectively. Similarly, Overall Radio- cytological concordance was 81.03%. In hormonal correlation, majority (59%) were euthyroid. In these lesions, 60.9% were goitres whereas in cases with hypothyroidism, majority (56%) had thyroiditis. Conclusion: FNAC is simple, cost-effective, more specific than sensitive procedure for evaluating thyroid masses, further evaluation of thyroid nodule for thyroid function status and radiological support especially in grey zone area of indeterminate lesion has a definitive role to play.